Improving Learning Outcomes and Learning Motivation in Mathematics Through Demonstration Methods with Number Card Media Assistance for Class I Students of SD Negeri 2 Samigaluh in Academic Year 2021/2022 - Siti Yawimah (IJCER (International Journal of Chemistry Education Research), 2023)
This study aims to improve the mathematics learning outcomes of class I students at SDN 2 Samigaluh for the 2021/2022 academic year. This type of research is Classroom Action Research which was carried out for 2 cycles with 2 meetings in each cycle. The results of the data in this study indicate that the learning outcomes of students have increased, namely, in cycle I, a percentage of 85.72% was obtained, and in cycle II a percentage of 100.00% was obtained. As for the results of the data on students' learning motivation, it showed a significant increase where in the first cycle the 1st meeting obtained a percentage of 52.57% and the 2nd meeting obtained a percentage of 72.94%. Whereas in cycle II, the 1st meeting obtained a percentage value of 85.51% and the 2nd meeting obtained a value of 90.11%. Thus, the use of the demonstration method using number card media aids can improve learning outcomes and learning motivation of class I students at SDN 2 Samigaluh in the mathematics subject for the 2021/2022 academic year.